Physiological and Biochemical Characterisation of Grape Rootstocks - Satisha, J.; Ramteke, S.D.; Karibasappa, G.S. (South African Journal of Enology and Viticulture, 2016)
Ten grape rootstocks were characterised for their various morphological, physiological and biochemical parameters. Significant differences were observed for most of the parameters studied. Rootstocks in the group of Vitis berlandierii × Vitis rupestris, such as 110 R, 1103 P, 99 R and B2-56, had a significantly higher content of total phenols, flavon-3- ols, flaveonoids, proline and total protein. Optimum C/N ratios in the mother vines of these rootstocks helped attain better rooting percentages of hardwood cuttings. Rootstocks such as Dog Ridge, 110 R, B2-56 and Salt Creek recorded the highest relative water content (RWC) and water-use efficiency (WUE) at single-leaf level, which is an important mechanism in overcoming drought tolerance. The high phenolic content in rootstocks such as Dog Ridge, 99 R, 110R and 1103 P may help in reducing the incidence of major grape diseases in commercial table varieties if grafted onto these rootstocks. This was established in our earlier studies of the incidence of powdery mildew in Thompson Seedless grafted onto different rootstocks. A significant and positive correlation was observed for WUE and total protein and proline content. Thus, the physio-biochemical characterisation of rootstocks may help to identify particular rootstocks that could influence a desired trait in commercial table / wine grape varieties after grafting.